PENGARUH SERVICE QUALITY DAN E-SERVICE QUALITY TERHADAP CUSTOMER SATISFACTION YANG DIMEDIASI OLEH PERCEIVED VALUE PADA PELANGGAN PT TIKI JALUR NUGRAHA EKAKURIR (JNE) DI KOTA BANDA ACEH - Putri Rahmalia; Syafruddin Chan (Jurnal Manajemen Inovasi, 2019)
This study aims to understand the influence of service quality, and e-service quality to customer satisfaction, as well as the role of perceived value as a mediator relationship. This study used a sample of 265 respondents who are customers of PT. Tiki Line Nugraha Ekakurir (JNE). Sampling technique using probability sampling with cluster sampling method. Structural equation model (SEM) is used as an analytical method to determine the effect of all the variables involved. The result of this research indicate that service quality variable have positive effect to perceived value, e-service quality have positive effect to perceived value, service quality have positive effect to customer satisfaction, e-service quality has no positive effect on Customer satisfaction, Perceived value has positive effect on customer satisfaction , and perceived value mediates service quality relationship to customer satisfaction, and also mediates e-service quality relationship to customer satisfaction.Keywords Service quality, E-service quality, Perceived value, Customer satisfaction